Effect of needle-free injection on psychological insulin resistance and insulin dosage in patients with type 2 diabetes - Wang, Weiping; Men, Lili; Wang, Yongbo; Shi, Chunhong; Yin, Huihui; Li, Han; Zhou, Haicheng; Du, Jianling (Frontiers in Endocrinology, 2024)
Background and objective Psychological insulin resistance (PIR), which refers to the reluctance of diabetic patients to use insulin, is a frequently encountered clinical issue. Needle-free injection (NFI) offers advantages in terms of expediting insulin absorption and mitigating adverse reactions related to injection. To evaluate the effects of subcutaneous injection of insulin aspart 30 with NFI on PIR and insulin dosage in patients with type 2 diabetes mellitus (T2DM). Methods Sixty-four patients with T2DM participated in this randomized, prospective, open, crossover study. Insulin aspart 30 was administered subcutaneously to each subject via QS-P NFI and Novo Pen 5 (NP) successively. The effects of NFI on PIR were analyzed. Differences in insulin dosage, glycemic variability, and injection safety were compared at similar levels of glycemic control. Results After the administration of NFI, the insulin treatment attitude scale score decreased (53.7 ± 7.3 vs. 58.9 ± 10.7, p<0.001), the insulin treatment adherence questionnaire score increased (46.3 ± 4.9 vs. 43.8 ± 7.1, p<0.001), and the insulin treatment satisfaction questionnaire score increased (66.6 ± 10.5 vs. 62.4 ± 16.5, p<0.001). At the same blood glucose level, NFI required a smaller dosage of insulin aspart 30 compared with that of NP (30.42 ± 8.70 vs. 33.66 ± 9.13 U/d, p<0.001). There were no differences in glycemic variability indices (standard deviation, mean amplitude of glycemic excursion or coefficient of variation) between the two injection methods. Compared with NP, NFI did not increase the incidence of hypoglycemia (17.2% vs. 14.1%, p=0.774), and it decreased the incidence of induration (4.7% vs. 23.4%, p=0.002) and leakage (6.3% vs. 20.3%, p=0.022) while decreasing the pain visual analog scale score (2.30 ± 1.58 vs. 3.11 ± 1.40, p<0.001). Conclusion NFI can improve PIR in patients with T2DM and be used with a smaller dose of insulin aspart 30 while maintaining the same hypoglycemic effect. Clinical trial registration https://www.chictr.org.cn/, identifier ChiCTR2400083658.